Implementasi Konsep ‘Reversion' pada Perancangan Interior Organic Living Center di Semarang - Vania, Christina; Sitinjak, Ronald Hasudungan Irianto; Suryanata, Linggajaya (Intra, 2018)
The degradation of environmental conditions and human health nowadays are getting worse, because of an instant lifestyle that leads people to keep using dangerous chemicals and not eco-friendly products. Therefore, organic products become the beneficial solution to enhance both people’s quality of life as well as the environment. People’s awareness towards a healthy and eco-friendlier lifestyle have also been increasing lately, but unfortunately this is not followed with the accessible source of information and organic products. Based on these phenomena, an educative recreational facility is needed to provide education in a fun way, as well as to introduce the variants and benefits of organic products in the market through multisensory experiences. Thus, designer initiated the Organic Living Center in Semarang, where education and information will be delivered through various interactive hands-on activities. The design method stages are: Observe, Define, Ideate, Evaluate, Prototype, Test & Implementation. The design concept called ‘Reversion’ applied by mimicking the characteristics of nature and also focusing on the connection with nature as the implementation of biophilic concept. Moreover, this project aims to generate positive impacts not only for people as consumer, but also support the local producers as a community, and the environment for the sustainability of life in the future.